Environmental heterogeneity promotes microgeographic genetic divergence in the Mediterranean killifish Aphanius fasciatus (Cyprinodontidae). Issue 4 (4th July 2017) - Angeletti, Dario; Cimmaruta, Roberta; Sebbio, Claudia; Bellisario, Bruno; Carere, Claudio; Nascetti, Giuseppe
Abstract : Environmental stress can promote evolutionary forces and genetic divergence, but at which microgeographic scale divergence may arise, even in the presence of gene flow, remains poorly known. We studied the effects of eutrophication in a saltwork over a period of 6 years on the gene pool of a local population of the Mediterranean killifish Aphanius fasciatus, a species resistant to extreme conditions. We hypothesised that during eutrophication, the environmental stress may have acted differently along a gradient of salinity and oxygen concentration in promoting evolutionary forces, generating divergence over a small spatial scale (2 km), despite gene flow. We analysed 24 allozymes in three temporal samples each composed of four spatial sub-samples, collected along the gradient, during eutrophication (2003 and 2005) and after a recovery project (2008). The results suggest that eutrophication promoted natural selection, originating a genetic cline on one locus (adenosine deaminase) significantly linked to salinity and oxygen concentration. Together with selection, both genetic drift and gene flow contributed to shaping the genetic structure under stress by further promoting the genetic heterogeneity and giving rise to deficits of heterozygotes as a secondary effect of the divergence. Environmental stress thus increased diversification, with the effects of selection and drift prevailing on gene flow. When environmental stress was relaxed (2008), allele and genotype frequencies became homogeneous, likely because under less extreme conditions the gene flow prevailed. These results improve our understanding of microgeographic divergence, and highlight the role of environmental stress in moulding microevolutionary dynamics and genetic patterns of animal populations.